Premacular Subhyaloid Haemorrhage Drainage by Frequency-Doubled (532 nm) Nd:YAG Laser - MK Rathore; Eva Tirkey; Shivcharan Lal Chandravanshi; Jainendra Shivdas Rahud; Rachhana Gupta (Delhi Journal of Ophthalmology)
Aim:- To evaluate the safety and efficacy of frequency-doubled Nd:YAG Laser hyaloidotomy in drainage of premacular subhyaloid haemorrhage of varied aetiology. Methods:- This was a retrospective study in which frequency-doubled Nd:YAG laser was used for draining entrapped premacular subhyaloid haemorrhage of varied aetiology into the vitreous cavity in 22 eyes of 18 patients by a single surgeon over a period of one year. In this series, visual acuity improvement was defined as an improvement of three or more lines on Snellen′s visual acuity chart. Results:- We found best visual acuity improvement in cases of anaemic and Valsalva retinopathy and limited improvement in proliferative and non proliferative diabetic retinopathy despite successful drainage of haemorrhage. Three eyes required two sitting and four eyes required higher energy for drainage. Conclusion:- Frequency-doubled Nd:YAG laser (532 nm) hyaloidotomy is a safe, simple and noninvasive procedure with a high success rate for the management of premacular subhyaloid haemorrhage. It is an effective, conservative and safer treatment modality for management of premacular subhyaloid haemorrhage.